Sealant composition, sealant, and method for producing and use thereof

CN123004337APending Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510560809.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明的目的是为了克服环氧密封胶的韧性差,耐溶剂性差、易析出失效的问题,提供一种密封胶组合物、密封胶及其制备方法和应用,该密封胶组合物的固化体系由聚醚胺和酚酞衍生物组成,聚醚胺提供柔性链段,酚酞衍生物同时含有氨基和羟基反应位点以及苯环和内酯,氨基和羟基提供化学交联点,内酯基团减弱苯环的共轭作用,防止刚度过大

Benefits of technology

[0016]通过上述技术方案,本发明提供的密封胶组合物、密封胶及其制备方法和应用具有以下有益效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004337A_ABST
    Figure CN123004337A_ABST
Patent Text Reader

Abstract

This invention relates to the field of sealants, and discloses a sealant composition, a sealant, a preparation method thereof, and its application; the sealant composition comprises independently existing components A and B; component A contains an epoxy resin; component B contains a polyetheramine, at least one phenolphthalein derivative of formula I, fully vulcanized powdered nitrile rubber, optionally an antioxidant, optionally a coupling agent, optionally a thixotropic agent, and a diluent; wherein the number average molecular weight of the polyetheramine is 200-3000 g / mol; wherein R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 R 11 R 12 Each of the following can be independently H, amino, methyl, or ethyl, R1-R 12 The number of amino groups is greater than or equal to 2; the sealant made from the composition of the present invention has high toughness and good solvent resistance, which meets the requirements for encapsulation of solvent-resistant film elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sealants, and more specifically, to a sealant composition, a sealant, a method for preparing the same, and its applications. Background Technology

[0002] Membrane separation technology is widely used in seawater desalination, drinking water purification, water quality improvement, oil-water separation, wastewater treatment, and chemical separation, purification, and concentration. Many industrial production processes involve the use of organic solvents, making efficient recovery and reuse of these solvents crucial. Solvent-resistant membrane separation technology offers a potential solution to these problems. Good sealing is a prerequisite for the long-term stable operation of membrane elements.

[0003] Epoxy resin sealant is a sealing material with excellent mechanical properties and simple processing, widely used in various sealing applications. This type of sealant has strong adhesion, high tensile strength, and also exhibits weather resistance and corrosion resistance, enabling bonding between most interfaces. From a molecular structure perspective, epoxy resin has numerous effective cross-linking sites formed by chemical cross-linking and benzene ring conjugation, resulting in stable chemical properties that meet the sealing requirements of solvent-resistant nanofiltration membrane elements. However, a large number of cross-linking sites often causes epoxy resin to lose toughness, leading to sealing failure. When using multifunctional or difunctional aromatic curing agents, the sealant becomes brittle, easily warping and damaging the membrane, resulting in membrane element failure. When using difunctional aliphatic curing agents, the sealant has low cross-linking density and poor solvent resistance, failing to meet the long-term stability requirements of solvent-resistant membrane elements. Therefore, the key issue is how to impart flexibility to epoxy resin while maintaining a large number of effective cross-linking sites.

[0004] There are three main methods to improve the flexibility of epoxy sealants: First, adding inorganic fillers with micro / nano structures, which induce slippage within the epoxy matrix, thus achieving a toughening effect. The problem is that as the amount of inorganic filler increases, the mechanical properties of the epoxy sealant matrix decrease significantly, and exceeding a certain dosage can easily lead to powdering. Second, adding small-molecule organic plasticizers, such as dibutyl phthalate, diisononyl phthalate, and diisodecyl phthalate, utilize their good compatibility with the epoxy sealant matrix to achieve uniform dispersion and weaken intermolecular forces, thereby achieving a toughening effect. The problem is that these toughening agents are prone to precipitation within the sealant matrix, leading to toughening failure. Third, adding macromolecular polymers, such as polyurethane, polyester, and liquid nitrile rubber, whose mechanism is similar to that of small-molecule ester toughening agents. These toughening agents also cannot avoid the problem of precipitation failure. Summary of the Invention

[0005] The purpose of this invention is to overcome the problems of poor toughness, poor solvent resistance, and easy precipitation failure of epoxy sealants, and to provide a sealant composition, sealant, its preparation method, and its application. The curing system of this sealant composition consists of polyetheramine and phenolphthalein derivatives. Polyetheramine provides flexible chain segments, while phenolphthalein derivatives contain both amino and hydroxyl reaction sites, as well as benzene rings and lactones. The amino and hydroxyl groups provide chemical crosslinking points, and the lactone groups weaken the conjugation effect of the benzene ring, preventing excessive stiffness. Therefore, the sealant made from the composition of this invention has high toughness and good solvent resistance, meeting the requirements for solvent-resistant membrane element encapsulation.

[0006] To achieve the above objectives, a first aspect of the present invention provides a sealant composition, wherein the sealant composition comprises component A and component B, which are present independently;

[0007] Component A contains epoxy resin;

[0008] Component B contains polyetheramine, at least one phenolphthalein derivative of Formula I, fully vulcanized powdered nitrile rubber, optionally an antioxidant, optionally a coupling agent, optionally a thixotropic agent, and a diluent;

[0009] The number-average molecular weight of the polyetheramine is 200-3000 g / mol.

[0010]

[0011] Among them, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 R 11 R 12 Each of the following is independently H, amino, methyl, or ethyl, R1-R 12 The number in the range is greater than or equal to 2.

[0012] A second aspect of the present invention provides a method for preparing a sealant, wherein the method includes: mixing component A and component B in a sealant composition, and then degassing and curing to obtain a sealant;

[0013] The sealant composition is the sealant composition described above.

[0014] A third aspect of the present invention provides a sealant prepared by the above method.

[0015] A fourth aspect of the present invention provides the application of the above-mentioned sealant in the sealing of membrane elements.

[0016] Through the above technical solutions, the sealant composition, sealant, preparation method and application provided by the present invention have the following beneficial effects.

[0017] In this invention, the sealant composition comprises polyetheramine, phenolphthalein derivative, and fully vulcanized powdered nitrile rubber. The polyetheramine provides flexible chain segments, while the phenolphthalein derivative contains both amino and hydroxyl reaction sites, as well as a benzene ring and a lactone. The amino and hydroxyl groups provide chemical crosslinking points, and the lactone groups weaken the conjugation effect of the benzene ring, preventing excessive stiffness. Therefore, the sealant made from the composition of this invention has high toughness and good solvent resistance, meeting the requirements for solvent-resistant membrane element encapsulation. Furthermore, the fully vulcanized powdered nitrile rubber in the composition improves the toughness of the sealant and avoids precipitation failure. Detailed Implementation

[0018] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0019] A first aspect of the present invention provides a sealant composition, wherein the sealant composition comprises component A and component B, which are present independently;

[0020] Component A contains epoxy resin;

[0021] Component B contains polyetheramine, at least one phenolphthalein derivative of Formula I, fully vulcanized powdered nitrile rubber, optionally an antioxidant, optionally a coupling agent, optionally a thixotropic agent, and a diluent;

[0022] The number-average molecular weight of the polyetheramine is 200-3000 g / mol.

[0023]

[0024] Among them, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 R 11 R 12 Each of the following is independently H, amino, methyl, or ethyl, R1-R 12 The number of amino groups is greater than or equal to 2.

[0025] In this invention, the sealant composition comprises polyetheramine, phenolphthalein derivative, and fully vulcanized powdered nitrile rubber. The polyetheramine provides flexible chain segments, while the phenolphthalein derivative contains both amino and hydroxyl reaction sites, as well as a benzene ring and a lactone. The amino and hydroxyl groups provide chemical crosslinking points, and the lactone groups weaken the conjugation effect of the benzene ring, preventing excessive stiffness. Therefore, the sealant made from the composition of this invention has high toughness and good solvent resistance, meeting the requirements for solvent-resistant membrane element encapsulation. Furthermore, the fully vulcanized powdered nitrile rubber in the composition improves the toughness of the sealant and avoids precipitation failure.

[0026] Furthermore, the number-average molecular weight of the polyetheramine is 400-2000 g / mol.

[0027] In this invention, there is no particular limitation on the type of polyetheramine, and conventional polyetheramines in the art can be used. For example, the polyetheramine is a commercially available polyetheramine, specifically, the polyetheramine can be selected from at least one of D230, D400, D1000 and D2000.

[0028] In this invention, the functionality of the polyetheramine is 2.

[0029] Furthermore, in Equation I, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 R 11 R 12 Each of them is independently H, amino, or methyl, R1-R 12 The number of amino groups is 2, R1-R 12 The number of methyl groups is less than or equal to 4.

[0030] Furthermore, in Formula I, R1 and R2 are amino groups, and R3, R4, R5, R6, R7, R8, R9, and R... 10 R 11 R 12 Each of them is independently H or methyl, R3-R 12 The number of methyl groups is less than or equal to 2.

[0031] According to a preferred embodiment of the present invention, in Formula I, R1 and R2 are amino groups, and R3, R4, R5, R6, R7, R8, R9, R... 10 R 11 R 12 For H.

[0032] According to the present invention, the epoxy resin is a bisphenol A type epoxy resin and / or a bisphenol F type epoxy resin.

[0033] In this invention, when the composition contains epoxy resins of the above types, the sealant made from the composition has good strength, toughness and solvent resistance.

[0034] According to the present invention, the epoxy equivalent of the epoxy resin is 90-500 g / eq.

[0035] In this invention, when the epoxy equivalent of the epoxy resin meets the above-mentioned range, the sealant made from the above composition has good strength and toughness.

[0036] Furthermore, the epoxy equivalent of the epoxy resin is 90-400 g / eq.

[0037] According to the present invention, the epoxy resin has a dynamic viscosity of 2000-12000 cps at 25°C.

[0038] In this invention, when the dynamic viscosity of the epoxy resin at 25°C meets the above-mentioned range, the sealant composition is easier to degas during processing and has good processability.

[0039] Furthermore, the epoxy resin has a dynamic viscosity of 3000-10000 cps at 25°C.

[0040] According to the present invention, the average particle size of the fully vulcanized powdered nitrile rubber is 20-2000 nm.

[0041] In this invention, when the average particle size of the fully vulcanized powdered nitrile rubber meets the above-mentioned range, the sealant made from the above composition has higher toughness.

[0042] Furthermore, the average particle size of the fully vulcanized powdered nitrile rubber is 20-1000 nm.

[0043] Furthermore, the average particle size of the fully vulcanized powdered nitrile rubber is 50-200 nm.

[0044] According to the present invention, in the fully vulcanized powdered nitrile rubber, the content of acrylonitrile structural units is 20-40 wt%, and the content of butadiene structural units is 60-80 wt%.

[0045] In this invention, when the content of acrylonitrile structural units and butadiene structural units meets the above-mentioned range, the sealant made from the above composition can take into account both toughness and solvent resistance.

[0046] Furthermore, in the fully vulcanized powdered nitrile rubber, the content of acrylonitrile structural units is 25-35 wt%, and the content of butadiene structural units is 65-75 wt%.

[0047] According to the present invention, the antioxidant is selected from phosphorus-based antioxidants and / or phenolic antioxidants.

[0048] In this invention, there is no particular limitation on the specific type of phosphorus-based antioxidant, and conventional choices in the field can be adopted. Preferably, the phosphorus-based antioxidant is selected from at least one of the following: bis(octadecyl)pentaerythritol diphosphite, triphenyl phosphate, dibutyl phosphate, tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triethyl phosphate, dioctyl phosphate, diisopropyl phosphate, diphenyl phosphate toluene ester, diphenyl phosphate mono-o-biphenyl ester, tri(butoxyethyl) phosphate, distearate pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, dicyclohexyl pentaerythritol diphosphite, tri(diethylphenyl) phosphite, tri(diisopropylphenyl) phosphite, tri(di-n-butylphenyl) phosphite, tri(2,6-di-tert-butylphenyl) phosphite, tri(2,4-di-tert-butylphenyl) phosphite, (bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite), and triphenyl phosphite. For example, the phosphorus-based antioxidant can be BASF's commercially available antioxidant 168 (tris(2,4-di-tert-butylphenyl) phosphite), ADK's commercially available PEP-8T (distearate pentaerythritol diphosphite) and PEP-36 (bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate), etc.

[0049] In this invention, there is no particular limitation on the specific type of phenolic antioxidant, and conventional selections in the art can be used. Preferably, the phenolic antioxidant is selected from octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,6-di-tert-butyl-4-methylphenol, 2,4-di-tert-butyl-6-methylphenol, tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate methane, 1,6-hexanediol-bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxybenzyl)propionate, etc. At least one of tert-butyl-4-hydroxyphenyl)propionate, 2-(1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl)-4,6-di-tert-pentylphenyl acrylate, 2,4-di-tert-butylphenol, 2,4-di-tert-pentylphenol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate isooctyl ester, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, isooctyl ester of 3,5-di-tert-butyl-4-hydroxyphenylpropionate, and 2,6-di-tert-butyl-p-cresol.

[0050] More specifically, the phenolic antioxidants are commercially available products, such as Irganox 1010 (pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate)), Irganox 1076 (octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), Irganox 1135 (isooctyl 3,5-di-tert-butyl-4-hydroxyphenylpropionate), Irganox 3114 (tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate), Irganox 1098 (N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexamethylenediamine) or Tinuvin 326 (2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole).

[0051] According to the present invention, the coupling agent is a silane coupling agent.

[0052] In this invention, there is no particular limitation on the specific type of silane coupling agent, and any conventional choice in the art can be used. Preferably, the coupling agent B is selected from at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-(2,3-epoxypropyl)propyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0053] According to the present invention, the thixotropic agent is selected from at least one of silica, bentonite, calcium carbonate, magnesium silicate, aluminum stearate, and calcium stearate. For example, the silica may be fumed silica.

[0054] In this invention, the diluent can be an active diluent or a non-active diluent. The active diluent can be a conventional choice in the art, for example, selected from at least one of butyl glycidyl ether, phenyl glycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, and trimethylolpropane triglycidyl ether. The non-active diluent can be a conventional choice in the art, for example, selected from at least one of butanone, methyl isopropyl ketone, methyl propyl ketone, dipropylene glycol dimethyl ether, dipropylene glycol methyl n-propyl ether, ethyl acetate, butyl acetate, isopropyl acetate, isobutyl acetate, propylene glycol diacetate, n-pentane, n-hexane, diethyl ether, and n-decane. To further improve the solvent resistance of the sealant, preferably, the diluent is an active diluent.

[0055] According to the present invention, the polyetheramine is 45-85 parts by weight, the phenolphthalein derivative is 1-10 parts by weight, the fully vulcanized powdered nitrile rubber is 5-50 parts by weight, the antioxidant is 0-2 parts by weight, the coupling agent is 0-7 parts by weight, the thixotropic agent is 0-30 parts by weight, and the diluent is 8-25 parts by weight.

[0056] In this invention, when the content of each component in component B meets the above-mentioned range, the sealant composition has good processability, and the sealant made from the above composition has high toughness and good solvent resistance, thus meeting the requirements for encapsulation of solvent-resistant film elements.

[0057] Further, the polyetheramine is 45-85 parts by weight, the phenolphthalein derivative is 1-10 parts by weight, the fully vulcanized powdered nitrile rubber is 5-50 parts by weight, the antioxidant is 0.1-2 parts by weight, the coupling agent is 1-5 parts by weight, the thixotropic agent is 5-30 parts by weight, and the diluent is 8-25 parts by weight.

[0058] Furthermore, the polyetheramine is 50-75 parts by weight, the phenolphthalein derivative is 2-8 parts by weight, the fully vulcanized powdered nitrile rubber is 10-40 parts by weight, the antioxidant is 0.5-1.5 parts by weight, the coupling agent is 3-5 parts by weight, the thixotropic agent is 5-25 parts by weight, and the diluent is 8-20 parts by weight.

[0059] According to a preferred embodiment of the present invention, the polyetheramine is 50-70 parts by weight, the phenolphthalein derivative is 2-6 parts by weight, the fully vulcanized powdered nitrile rubber is 10-30 parts by weight, the antioxidant is 0.5-1.5 parts by weight, the coupling agent is 3-5 parts by weight, the thixotropic agent is 5-25 parts by weight, and the diluent is 8-20 parts by weight.

[0060] According to the present invention, component A further comprises an antifoaming agent.

[0061] In this invention, when component A contains a defoamer, it is beneficial to mix component A and component B evenly and to defoam more easily; and the sealant made from the above composition has better sealing performance, toughness and strength.

[0062] In this invention, there is no particular limitation on the specific type of defoamer, and any conventional choice in the art can be used. For example, the defoamer can be at least one of defoamer BYK141, defoamer BYK333, defoamer BYK354, and defoamer BYK066N.

[0063] According to the present invention, in component A, the epoxy resin is 85-95 parts by weight and the defoamer is 0.2-1.5 parts by weight.

[0064] Further, in component A, the epoxy resin is 85-95 parts by weight, and the defoamer is 0.2-1 parts by weight.

[0065] According to the present invention, the mass ratio of component A to component B is 1:0.2-0.7.

[0066] In this invention, when the mass ratio of component A to component B meets the above-mentioned range, the curing reaction of the epoxy is relatively complete. For example, the mass ratio of component A to component B is 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, or 1:0.7.

[0067] Furthermore, the mass ratio of component A to component B is 1:0.3-0.6.

[0068] A second aspect of the present invention provides a method for preparing a sealant, wherein the method includes: mixing component A and component B in a sealant composition, and then degassing and curing to obtain a sealant;

[0069] The sealant composition is the sealant composition described above.

[0070] According to the present invention, the degassing conditions are as follows: the degassing time is 5-20 min, and the vacuum degree is -0.05 MPa to -0.5 MPa.

[0071] In this invention, the mixing conditions for component A and component B include: a mixing temperature of 35-45℃ and a mixing time of 20-180 min.

[0072] According to the present invention, component B is a premixed component B.

[0073] According to the present invention, the method includes the following steps:

[0074] (1) Component A is first stirred and degassed to obtain premixed component A;

[0075] (2) Component B is subjected to a second stirring and degassing to obtain premixed component B;

[0076] (3) Mix premixed component A and premixed component B, and after degassing and curing, obtain sealant.

[0077] In this invention, when stepwise mixing is used, it is beneficial to mix the components evenly, which helps to improve the toughness and solvent resistance of the sealant.

[0078] In this invention, the degassing conditions in steps (1) and (2) include: a degassing time of 5-20 min and a vacuum degree of -0.05 MPa to -0.5 MPa. The degassing conditions in steps (1) and (2) can be the same or different.

[0079] In this invention, in step (1), the conditions for the first stirring include: a temperature of 25℃-80℃, preferably 30℃-60℃.

[0080] In this invention, in step (2), the conditions for the second stirring include: a temperature of 25-60°C, preferably 30-40°C.

[0081] In this invention, there are no special limitations on the curing conditions, and those skilled in the art can adjust them according to the actual situation. Preferably, the curing conditions include: a temperature of 25-30℃ and a curing time of 20-28h.

[0082] A third aspect of the present invention provides a sealant prepared by the above method.

[0083] In this invention, the tensile strength of the sealant is greater than or equal to 27 MPa.

[0084] In this invention, the elongation at break of the sealant is greater than or equal to 8%.

[0085] In this invention, a higher elongation at break of the sealant indicates better toughness, i.e., better sealing performance. When both the tensile strength and elongation at break of the sealant meet the above-mentioned ranges, it indicates that the sealant has a lower modulus, better toughness, and is suitable for sealing membrane elements.

[0086] Furthermore, the tensile strength of the sealant is 30-40 MPa.

[0087] Furthermore, the elongation at break of the sealant is greater than or equal to 10%.

[0088] In this invention, the shear strength of the sealant is greater than or equal to 14 MPa.

[0089] A fourth aspect of the present invention provides the application of the above-mentioned sealant in the sealing of membrane elements.

[0090] In the following implementation columns and comparative examples:

[0091] Epoxy resin (bisphenol A type): Nan Ya Epoxy Resin Factory, grade: NPEL-127E, epoxy equivalent is 180g / eq, and dynamic viscosity at 25℃ is 9000cps.

[0092] Epoxy resin (bisphenol F type): Nan Ya Epoxy Resin Factory, grade NPEF-176, epoxy equivalent is 180g / eq, and dynamic viscosity is 4000cps at 25℃.

[0093] Epoxy resin (bisphenol A type): Nan Ya Epoxy Resin Factory, grade NPEL-128S, epoxy equivalent is 210g / eq, and dynamic viscosity is 22000cps at 25℃.

[0094] Polyetheramine 1: Huntsman, brand name D400, number average molecular weight 400 g / mol, functionality 2.

[0095] Polyetheramine 2: Huntsman, brand name D2000, number average molecular weight of 2000 g / mol, functionality of 2.

[0096] Polyetheramine 3: Huntsman, brand name D1000, number average molecular weight is 1000 g / mol, functionality is 2.

[0097] Polyetheramine 4: Huntsman, brand name D230, number average molecular weight is 230 g / mol, functionality is 2.

[0098] The preparation methods of diaminophenolphthalein (DAP) include:

[0099] (1) Synthesis of 3,3'-dinitrophenolphthalein (DNP)

[0100] Phenolphthalein monomer (2.0 g, 6.24 mmol) was weighed and added to a 200 mL flask, followed by 60 mL of acetic acid solution. The mixture was stirred for 20 min to ensure complete dissolution. Then, granular crystals of Y(NO3)3·6H2O (2.4 g, 6.24 mmol) were added to the mixture. The reaction progress was monitored by thin-layer chromatography (TLC) in petroleum benzene containing 10 wt% ethyl acetate (EtOAc) under vigorous stirring at room temperature (25 °C) for one hour. The resulting mixture was then poured into a flask containing 600 mL of ice-cold deionized water. A large amount of pale yellow precipitate formed at the bottom of the flask. The mixture was stirred for one hour to allow sufficient exchange between the acetic acid and deionized water. The resulting mixture was filtered and repeatedly washed with ice-cold deionized water until the filtrate became colorless and transparent. The filter cake was placed in a vacuum oven at 60 °C for 24 hours to obtain a pale yellow solid. NMR spectroscopy confirmed the formation of 3,3'-dinitrophenolphthalein.

[0101] (2) Synthesis of 3,3'-Diaminophenolphthalein (DAP)

[0102] Weigh 5.0 g (12.25 mL) of the obtained 3,3'-dinitrophenolphthalein into a 250 mL three-necked round-bottom flask. Add 30 mL of tetrahydrofuran (THF) to the flask and stir for approximately 25 minutes until the 3,3'-dinitrophenolphthalein is completely dissolved. Then, add 20 mL of ethanol and stir thoroughly until homogeneous. Next, add 0.5 g of 10% Pd / C catalyst to the mixture. Seal the reaction apparatus completely and evacuate the system for 10-20 minutes until a complete vacuum is achieved. Introduce hydrogen gas into the sealed apparatus and slowly increase the temperature to 60 °C for 12 hours. After the reaction is complete, cool the reaction solution to room temperature. Use a Buchner funnel lined with diatomaceous earth to filter the mixture and remove the residue, which is mainly the Pd / C catalyst. The obtained transparent brownish-red filtrate was poured into a 250 mL round-bottom flask and heated to 50 °C in a water bath under N2 protection. While stirring continuously, 15 mL of deionized water was added dropwise to the filtrate until the solution reached its cloud point. The mixture was then allowed to cool at 5 °C for 12 h to crystallize. The crystals were rinsed with deionized water (1 °C) and the grayish-white crystals were removed. The filter residue was dried in a vacuum oven at 50 °C for 24 h to obtain a grayish-white powder. NMR confirmed the presence of 3,3'-diaminophenolphthalein (in Formula I, R1 and R2 are amino groups, R3, R4, R5, R6, R7, R8, R9, R...). 10 R 11 R 12 (for H)

[0103] Fully vulcanized powdered nitrile butadiene rubber: The preparation method includes: placing 2 kg of commercially available nitrile butadiene latex (brand: Feisheng) with a solid content of 55 wt% in a container, adding 30 g of isooctyl acrylate dropwise while stirring, and continuing stirring for 2 hours after the addition is complete. Then, irradiate with a cobalt source at a dose of 2.5 Mrad and a dose rate of 50 Gy / min. The mixture is then spray-dried using a spray dryer with an inlet temperature of 140°C and an outlet temperature of 50°C. The dried fully vulcanized powdered nitrile butadiene rubber is collected in a cyclone separator. The average particle size of the fully vulcanized powdered nitrile butadiene rubber is 60 nm. In the crosslinked powdered nitrile butadiene rubber, the content of acrylonitrile structural units is 34 wt%, and the content of butadiene structural units is 66 wt%.

[0104] Fully vulcanized powdered styrene-butadiene rubber (SBR): The preparation method includes: placing 2 kg of commercially available SBR latex (brand: Deqiao) with a solid content of 48 wt% in a container, and adding 30 g of isooctyl acrylate dropwise while stirring. After the addition is complete, stirring continues for 2 hours. Then, the mixture is irradiated with a cobalt source at a dose of 2.5 Mrad and a dose rate of 50 Gy / min. The mixture is then spray-dried using a spray dryer with an inlet temperature of 140°C and an outlet temperature of 50°C. The dried powdered SBR is collected in a cyclone separator. The average particle size of the fully vulcanized powdered SBR is 66 nm.

[0105] Antioxidant: BASF, brand name Antioxidant 168.

[0106] Coupling agent: Dow Corning, γ-(2,3-epoxypropyl)propyltrimethoxysilane, brand name KH560.

[0107] Thixotropic agent (fumed silica): Cabot, grade M-5.

[0108] Diluent: Hubei Chengfeng Chemical Co., Ltd., n-Butyl glycidyl ether.

[0109] Defoamer: BYK Chemical, brand name BYK141.

[0110] Tensile strength and elongation at break: Tensile samples were prepared in accordance with GB / T 2567-2008 "Test Methods for Properties of Resin Castings", and tensile tests were conducted using an electronic universal testing machine to determine the mechanical properties.

[0111] Shear strength: Samples were prepared and tested in accordance with GB / T 7124-2008 "Adhesives - Determination of tensile shear strength (rigid material to rigid material)".

[0112] Solvent resistance test method for sealant: Immerse the sample in ethyl acetate at room temperature for 10 days, then remove it and test the tensile strength and elongation at break of the sealant.

[0113] In the following examples and comparative examples, "parts" are weighed by mass, where 1 part is 10g.

[0114] In the following examples and comparative examples, the room temperature is 25°C.

[0115] Example 1

[0116] Component A: Mix 95 parts of epoxy resin (bisphenol A type, NPEL-127E) and 1 part of defoamer BYK141 at 40℃, stir evenly, and remove bubbles under vacuum (defoaming time is 10 min, vacuum degree is -0.05MPa) to obtain component A.

[0117] Component B: 60 parts of polyetheramine D2000, 5 parts of diaminophenolphthalein (DAP), 15 parts of fully vulcanized powdered nitrile rubber, 1 part of antioxidant (brand name 168), 4 parts of γ-(2,3-epoxypropyl)propyltrimethoxysilane (KH560), 9 parts of thixotropic agent (fumed silica) and 10 parts of diluent (n-butyl glycidyl ether) were mixed evenly at 30°C, and degassed under vacuum (degassed for 10 min, vacuum degree of -0.05 MPa) to obtain component B.

[0118] 100 parts of component A and 40 parts of component B (mass ratio of component A to component B is 1:0.4) prepared above were mixed (40℃, 30 min), degassed (degassed time was 10 min, vacuum degree was -0.05 MPa), and cured at room temperature for 24 h to obtain sealant N1. The performance test structure is shown in Table 1.

[0119] Example 2

[0120] Component A: Mix 95 parts of epoxy resin (bisphenol F type, NPEF-176) and 1 part of defoamer BYK141 at 40℃, stir evenly, and degas under vacuum (degassing time is 10 min, vacuum degree is -0.05 MPa) to obtain component A.

[0121] Component B: 60 parts of polyetheramine D2000, 5 parts of diaminophenolphthalein (DAP), 15 parts of fully vulcanized powdered nitrile rubber, 1 part of antioxidant (brand name 168), 4 parts of γ-(2,3-epoxypropyl)propyltrimethoxysilane (KH560), 9 parts of thixotropic agent (fumed silica) and 10 parts of diluent (n-butyl glycidyl ether) were mixed evenly at 30°C, and degassed under vacuum (degassed for 10 min, vacuum degree of -0.05 MPa) to obtain component B.

[0122] 100 parts of component A and 40 parts of component B (mass ratio of component A to component B is 1:0.4) prepared above were mixed (40℃, 30 min), degassed (degassed time was 10 min, vacuum degree was -0.05 MPa), and cured at room temperature for 24 h to obtain sealant N2. The performance test results are shown in Table 1.

[0123] Example 3

[0124] Component A: Mix 95 parts of epoxy resin (bisphenol A type, NPEL-127E) and 1 part of defoamer BYK141 at 40℃, stir evenly, and remove bubbles under vacuum (defoaming time is 10 min, vacuum degree is -0.05MPa) to obtain component A.

[0125] Component B: 60 parts of polyetheramine D1000, 5 parts of diaminophenolphthalein (DAP), 15 parts of fully vulcanized powdered nitrile rubber, 1 part of antioxidant (brand name 168), 4 parts of γ-(2,3-epoxypropyl)propyltrimethoxysilane (KH560), 9 parts of thixotropic agent (fumed silica) and 10 parts of diluent (n-butyl glycidyl ether) were mixed evenly at 30°C, and degassed under vacuum (degassed for 10 min, vacuum degree of -0.05 MPa) to obtain component B.

[0126] 100 parts of component A and 40 parts of component B (mass ratio of component A to component B is 1:0.4) prepared above were mixed (40℃, 30 min), degassed (degassed time was 10 min, vacuum degree was -0.05 MPa), and cured at room temperature for 24 h to obtain sealant N3. The performance test structure is shown in Table 1.

[0127] Example 4

[0128] Component A: Mix 95 parts of epoxy resin (bisphenol A type, NPEL-127E) and 1 part of defoamer BYK141 at 40℃, stir evenly, and remove bubbles under vacuum (defoaming time is 10 min, vacuum degree is -0.05MPa) to obtain component A.

[0129] Component B: 60 parts of polyetheramine D2000, 7 parts of diaminophenolphthalein (DAP), 15 parts of fully vulcanized powdered nitrile rubber, 1 part of antioxidant (brand name 168), 4 parts of γ-(2,3-epoxypropyl)propyltrimethoxysilane (KH560), 9 parts of thixotropic agent (fumed silica) and 8 parts of diluent (n-butyl glycidyl ether) were mixed evenly at 30°C, and degassed under vacuum (degassed for 10 min, vacuum degree of -0.05 MPa) to obtain component B.

[0130] 100 parts of component A and 40 parts of component B (mass ratio of component A to component B is 1:0.4) prepared above were mixed (40℃, 30 min), degassed (degassed time was 10 min, vacuum degree was -0.05 MPa), and cured at room temperature for 24 h to obtain sealant N4. The performance test results are shown in Table 1.

[0131] Example 5

[0132] Component A: Mix 95 parts of epoxy resin (bisphenol A type, NPEL-127E) and 1 part of defoamer BYK141 at 40℃, stir evenly, and remove bubbles under vacuum (defoaming time is 10 min, vacuum degree is -0.05MPa) to obtain component A.

[0133] Component B: 60 parts of polyetheramine D2000, 3 parts of diaminophenolphthalein (DAP), 15 parts of fully vulcanized powdered nitrile rubber, 1 part of antioxidant (brand name 168), 4 parts of γ-(2,3-epoxypropyl)propyltrimethoxysilane (KH560), 9 parts of thixotropic agent (fumed silica) and 12 parts of diluent (n-butyl glycidyl ether) were mixed evenly at 30°C, and the mixture was degassed under vacuum (degassed for 10 min at a vacuum degree of -0.05 MPa) to obtain component B.

[0134] 100 parts of component A and 40 parts of component B (mass ratio of component A to component B is 1:0.4) prepared above were mixed (40℃, 30 min), degassed (degassed time was 10 min, vacuum degree was -0.05 MPa), and cured at room temperature for 24 h to obtain sealant N5. The performance test structure is shown in Table 1.

[0135] Example 6

[0136] Component A: Mix 95 parts of epoxy resin (bisphenol A type, NPEL-127E) and 1 part of defoamer BYK141 at 40℃, stir evenly, and remove bubbles under vacuum (defoaming time is 10 min, vacuum degree is -0.05MPa) to obtain component A.

[0137] Component B: 55 parts of polyetheramine D2000, 5 parts of diaminophenolphthalein (DAP), 20 parts of fully vulcanized powdered nitrile rubber, 1 part of antioxidant (brand name 168), 4 parts of γ-(2,3-epoxypropyl)propyltrimethoxysilane (KH560), 9 parts of thixotropic agent (fumed silica) and 10 parts of diluent (n-butyl glycidyl ether) were mixed evenly at 30°C, and degassed under vacuum (degassed for 10 min, vacuum degree of -0.05 MPa) to obtain component B.

[0138] 100 parts of component A and 40 parts of component B (mass ratio of component A to component B is 1:0.4) prepared above were mixed (40℃, 30 min), degassed (degassed time was 10 min, vacuum degree was -0.05 MPa), and cured at room temperature for 24 h to obtain sealant N6. The performance test structure is shown in Table 1.

[0139] Example 7

[0140] Component A: Mix 95 parts of epoxy resin (bisphenol A type, NPEL-127E) and 1 part of defoamer BYK141 at 40℃, stir evenly, and remove bubbles under vacuum (defoaming time is 10 min, vacuum degree is -0.05MPa) to obtain component A.

[0141] Component B: 65 parts of polyetheramine D2000, 5 parts of diaminophenolphthalein (DAP), 10 parts of fully vulcanized powdered nitrile rubber, 1 part of antioxidant (brand name 168), 4 parts of γ-(2,3-epoxypropyl)propyltrimethoxysilane (KH560), 9 parts of thixotropic agent (fumed silica) and 10 parts of diluent (n-butyl glycidyl ether) were mixed evenly at 30°C, and degassed under vacuum (degassed for 10 min, vacuum degree of -0.05 MPa) to obtain component B.

[0142] 100 parts of component A and 40 parts of component B (mass ratio of component A to component B is 1:0.4) prepared above were mixed (40℃, 30 min), degassed (degassed time was 10 min, vacuum degree was -0.05 MPa), and cured at room temperature for 24 h to obtain sealant N7. The performance test results are shown in Table 1.

[0143] Example 8

[0144] The sealant was prepared according to the method of Example 1, except that component B consisted of 80 parts polyetheramine D2000, 10 parts diaminophenolphthalein (DAP), 50 parts fully vulcanized powdered nitrile rubber, 1 part antioxidant (brand name 168), 4 parts γ-(2,3-epoxypropyl)propyltrimethoxysilane (KH560), 9 parts thixotropic agent (fumed silica), and 10 parts diluent (n-butyl glycidyl ether). Sealant N8 was prepared, and its performance test structure is shown in Table 1.

[0145] Example 9

[0146] The sealant was prepared according to the method of Example 1, except that component B consisted of 80 parts polyetheramine D2000, 10 parts diaminophenolphthalein (DAP), 15 parts fully vulcanized powdered nitrile rubber, 1 part antioxidant (brand name 168), 4 parts γ-(2,3-epoxypropyl)propyltrimethoxysilane (KH560), 9 parts thixotropic agent (fumed silica), and 10 parts diluent (n-butyl glycidyl ether). Sealant N9 was prepared, and its performance test structure is shown in Table 1.

[0147] Example 10

[0148] The sealant was prepared according to the method of Example 1, except that the epoxy resin in component A was a bisphenol A type epoxy resin (brand name NPEL-128S).

[0149] The sealant N10 was prepared, and the performance test structure is shown in Table 1.

[0150] Example 11

[0151] The sealant was prepared according to the method of Example 1, except that component A contained 95 parts epoxy resin (bisphenol A type, NPEL-127E) and 1 part defoamer BYK141; component B contained 60 parts polyetheramine D2000, 5 parts diaminophenolphthalein (DAP), 15 parts fully vulcanized powdered nitrile rubber, 1 part antioxidant (brand name 168), 4 parts γ-(2,3-epoxypropyl)propyltrimethoxysilane (KH560), 9 parts thixotropic agent (fumed silica), and 10 parts diluent (n-butyl glycidyl ether). Components A and B were mixed at a mass ratio of 1:0.4 (40°C, 30 min), degassed (degassed for 10 min, vacuum degree -0.05 MPa), and cured at room temperature for 24 h to obtain sealant N11. The performance test results are shown in Table 1.

[0152] Example 12

[0153] The sealant was prepared according to the method of Example 1, except that component A contained 100 parts of epoxy resin (bisphenol A type, NPEL-127E) and did not contain defoamer; the resulting sealant was N12. The performance test results are shown in Table 1.

[0154] Comparative Example 1

[0155] The sealant was prepared according to the method of Example 1, except that fully vulcanized powdered nitrile rubber was not added to component B.

[0156] Sealant D1 was prepared, and the performance test structure is shown in Table 1.

[0157] Comparative Example 2

[0158] The sealant was prepared according to the method of Example 1, except that polyetheramine was not added to component B.

[0159] The sealant D2 was prepared, and the performance test structure is shown in Table 1.

[0160] Comparative Example 3

[0161] The sealant was prepared according to the method of Example 1, except that the polyetheramine used in component B was polyetheramine D230.

[0162] The sealant D3 was prepared, and the performance test structure is shown in Table 1.

[0163] Comparative Example 4

[0164] The sealant was prepared according to the method of Example 1, except that diaminophenolphthalein (DAP) was not added to component B.

[0165] The sealant D4 was prepared, and the performance test structure is shown in Table 1.

[0166] Comparative Example 5

[0167] The sealant was prepared according to the method of Example 1, except that diaminophenolphthalein (DAP) in component B was replaced with 3,3'-dihydroxybenzidine.

[0168] The sealant D5 was prepared, and the performance test structure is shown in Table 1.

[0169] Comparative Example 6

[0170] The sealant was prepared according to the method of Example 1, except that the fully vulcanized powdered nitrile rubber in component B was replaced with dioctyl phthalate.

[0171] The sealant D6 was prepared, and the performance test structure is shown in Table 1.

[0172] Comparative Example 7

[0173] The sealant was prepared according to the method of Example 1, except that the polyetheramine and diaminophenolphthalein in component B were replaced with an equal mass of m-phenylenediamine.

[0174] The sealant D7 was prepared, and the performance test structure is shown in Table 1.

[0175] Comparative Example 8

[0176] The sealant was prepared according to the method of Example 1, except that the fully vulcanized powdered nitrile rubber in component B was replaced with fully vulcanized powdered styrene-butadiene rubber.

[0177] The sealant D8 was prepared, and the performance test structure is shown in Table 1.

[0178] Table 1

[0179]

[0180] The results in Table 1 show that the sealant of this invention, while maintaining high tensile strength, exhibits a significantly improved elongation at break compared to the comparative examples, indicating good toughness and thus good sealing performance. After solvent immersion treatment, the strength and elongation at break did not change significantly, demonstrating better performance compared to the comparative examples. In contrast, Comparative Example 6, which used dioctyl phthalate as a plasticizer, showed a significant decrease in elongation at break after solvent immersion, indicating that conventional liquid plasticizers are prone to precipitation. Comparative Example 7, using the conventional epoxy crosslinking system m-phenylenediamine, produced a sealant with high strength but low elongation at break and excessively high modulus (stiffness), unsuitable for membrane element sealing. Comparative Example 8, using fully vulcanized powdered styrene-butadiene rubber, exhibited poor compatibility with epoxy, failing to provide adequate toughening, resulting in lower tensile strength and elongation at break.

[0181] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A sealant composition, characterized in that, The sealant composition comprises component A and component B, which are present independently. Component A contains epoxy resin; Component B contains polyetheramine, at least one phenolphthalein derivative of Formula I, fully vulcanized powdered nitrile rubber, optionally an antioxidant, optionally a coupling agent, optionally a thixotropic agent, and a diluent; The number-average molecular weight of the polyetheramine is 200-3000 g / mol. Among them, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 R 11 R 12 Each of the following is independently H, amino, methyl, or ethyl, R1-R 12 The number of amino groups is greater than or equal to 2.

2. The sealant composition according to claim 1, wherein, In Equation I, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 R 11 R 12 Each of them is independently H, amino, or methyl, R1-R 12 The number of amino groups is 2, R1-R 12 The number of methyl groups in the middle group is less than or equal to 4; Preferably, in Formula I, R1 and R2 are amino groups, and R3, R4, R5, R6, R7, R8, R9, R... 10 R 11 R 12 Each of them is independently H or methyl, R3-R 12 The number of methyl groups is less than or equal to 2; Preferably, the epoxy resin is bisphenol A type epoxy resin and / or bisphenol F type epoxy resin; Preferably, the epoxy equivalent of the epoxy resin is 90-500 g / eq, more preferably 90-400 g / eq; Preferably, the epoxy resin has a dynamic viscosity of 2000-12000 cps at 25°C, and more preferably 3000-10000 cps.

3. The sealant composition according to claim 1 or 2, wherein, The number-average molecular weight of the polyetheramine is 400-2000 g / mol; Preferably, the average particle size of the fully vulcanized powdered nitrile rubber is 20-2000 nm, more preferably 20-1000 nm, and even more preferably 50-200 nm; Preferably, in the fully vulcanized powdered nitrile rubber, the content of acrylonitrile structural units is 20-40 wt%, preferably 25-35 wt%, and the content of butadiene structural units is 60-80 wt%, preferably 65-75 wt%. Preferably, the antioxidant is selected from phosphorus-based antioxidants and / or phenolic antioxidants; Preferably, the coupling agent is a silane coupling agent; Preferably, the thixotropic agent is selected from at least one of silicon dioxide, bentonite, calcium carbonate, magnesium silicate, aluminum stearate, and calcium stearate.

4. The sealant composition according to any one of claims 1-3, wherein, The polyetheramine is 45-85 parts by weight, the phenolphthalein derivative is 1-10 parts by weight, the fully vulcanized powdered nitrile rubber is 5-50 parts by weight, the antioxidant is 0-2 parts by weight, the coupling agent is 0-7 parts by weight, the thixotropic agent is 0-30 parts by weight, and the diluent is 8-25 parts by weight. Preferably, the polyetheramine is 45-85 parts by weight, the phenolphthalein derivative is 1-10 parts by weight, the fully vulcanized powdered nitrile rubber is 5-50 parts by weight, the antioxidant is 0.1-2 parts by weight, the coupling agent is 1-5 parts by weight, the thixotropic agent is 5-30 parts by weight, and the diluent is 8-25 parts by weight. More preferably, the polyetheramine is 50-75 parts by weight, the phenolphthalein derivative is 2-8 parts by weight, the fully vulcanized powdered nitrile rubber is 10-40 parts by weight, the antioxidant is 0.5-1.5 parts by weight, the coupling agent is 3-5 parts by weight, the thixotropic agent is 5-25 parts by weight, and the diluent is 8-20 parts by weight. Preferably, the mass ratio of component A to component B is 1:0.2-0.

7.

5. The sealant composition according to any one of claims 1-4, wherein, Component A also contains an antifoaming agent; Preferably, in component A, the epoxy resin is 85-95 parts by weight and the defoamer is 0.2-1.5 parts by weight.

6. A method for preparing a sealant, characterized in that, The method includes: mixing component A and component B in a sealant composition, and then degassing and curing to obtain a sealant; Wherein, the sealant composition is the sealant composition according to any one of claims 1-5.

7. The method according to claim 6, wherein, The degassing conditions are as follows: degassing time is 5-20 min, and vacuum degree is -0.05 MPa to -0.5 MPa; Preferably, component B is a premixed component B.

8. The method according to claim 6 or 7, wherein, The method includes the following steps: (1) Component A is first stirred and degassed to obtain premixed component A; (2) Component B is subjected to a second stirring and degassing to obtain premixed component B; (3) Mix premixed component A and premixed component B, and after degassing and curing, obtain sealant.

9. A sealant made by the method according to any one of claims 6-8.

10. The application of the sealant according to any one of claims 1-5 and 9 in the sealing of membrane elements.